Paternal diet impairs F1 and F2 offspring vascular function through sperm and seminal plasma specific mechanisms in mice. (15th October 2019) - Morgan, Hannah L.; Paganopoulou, Panaigota; Akhtar, Sofia; Urquhart, Natalie; Philomin, Ranmini; Dickinson, Yasmin; Watkins, Adam J.
Abstract : Key points: A low protein diet had minimal effects on paternal cardiovascular function or renin–angiotensin system activity. Paternal low protein diet modified F1 neonatal and adult offspring renin–angiotensin system activity and cardiovascular function in a sperm and/or seminal plasma specific manner. Paternal low protein diet modified F1 male offspring testicular expression of central epigenetic regulators. Significant changes in F2 neonatal offspring growth and tissue angiotensin‐converting enzyme activity were programmed by paternal low protein diet in a sperm and/or seminal plasma specific manner. Abstract: Although the impact of maternal diet on adult offspring health is well characterized, the role that a father's diet has on his offspring's health remains poorly defined. We establish the significance of a sup‐optimal paternal low protein diet for offspring vascular homeostasis and define the sperm and seminal plasma specific programming effects on cardiovascular health. Male C57BL6 mice were fed either a control normal protein diet (NPD; 18% protein) or an isocaloric low protein diet (LPD; 9% protein) for a minimum of 7 weeks. Using artificial insemination, in combination with vasectomized male mating, we generated offspring derived from either NPD or LPD sperm (devoid of seminal plasma) but in the presence of NPD or LPD seminal plasma (devoid of sperm). We observed that either LPD sperm or seminal fluid at conception impaired adult offspring vascular function in response to both vasoconstrictors and dilators. Underlying these changes in vascular function were significant changes in serum, lung and kidney angiotensin‐converting enzyme (ACE) activity, established in F1 offspring from 3 weeks of age, maintained into adulthood and present also within juvenile F2 offspring. Furthermore, we observed differential expression of multiple central renin–angiotensin system regulators in adult offspring kidneys. Finally, paternal diet modified the expression profiles of central epigenetic regulators of DNA methylation, histone modifications and RNA methylation in adult F1 male testes. These novel data reveal the impact of sub‐optimal paternal nutrition on offspring cardiovascular well‐being, programming offspring cardiovascular function through both sperm and seminal plasma specific mechanisms over successive generations. Key points: A low protein diet had minimal effects on paternal cardiovascular function or renin–angiotensin system activity. Paternal low protein diet modified F1 neonatal and adult offspring renin–angiotensin system activity and cardiovascular function in a sperm and/or seminal plasma specific manner. Paternal low protein diet modified F1 male offspring testicular expression of central epigenetic regulators. Significant changes in F2 neonatal offspring growth and tissue angiotensin‐converting enzyme activity were programmed by paternal low protein diet in a sperm and/or seminal plasma specific manner.